PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI MODEL COOOPERATIVE LEARNING TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA MATA PELAJARAN IPS TERPADU KELAS VII SMP NEGERI 2 ASEMBAGUS SEMESTER GENAP - Miftahus Surur (STKIP PGRI SITUBONDO, 2016)
Low learning activity on Integrated Social Science subject adversely affects student’s learning outcomes. One factor that affect student’s learning outcomes was learning model which implemented by teacher. The objective of this research was enhanced student’s learning activity and their learning outcome on Integrated Social Science subject by the implementation of cooperative learning model with Team Assisted Individualization (TAI). This research was conducted since May 12th, 2016 until May 21st, 2016 with research object was students Class VII-B as many as 24 students. The research design was Hopkins scheme model, by using 4 phases, which were planning, action, observation, and reflection. To collect data, this research used some techniques, which were observation, interview, and test. The data analysis of this research was used qualitative descriptive analysis. The result of this research showed that student’s learning activity and their learning outcomes was enhanced. Before the implementation of learning model, student’s learning activity was on medium criteria. Based on the result of daily test analysis on the first cycle, student’s classical mastery degree was 77,86%. It showed that the implementation of cooperative learning model with Team Assisted Individualization (TAI) on the first cycle was not succeeded, so this research will be continued to the second cycle. And, the result of daily test analysis on the second cycle, student’s classical mastery degree was 91,14%. Students succeed on the second cycle daily test showed that the implementation of cooperative learning model with Team Assisted Individualization (TAI) was succeeded and brought students to get maximum learning outcomes. Based on the result of this research and its discussions, it can be concluded that the implementation of cooperative learning model with Team Assisted Individualization (TAI) was proved can enhanced student’s learning activity and their learning outcomes on Integrated Social Science subject with classical mastery degree 91,14%.